Autoimmune inner ear disease secondary to Hashimoto's thyroiditis: a case report - Beenish Fayyaz; Sunita Upreti (Greater Baltimore Medical Center, 2018)
Autoimmune inner ear disease is an important yet incompletely understood cause of hearing loss which can present to different medical disciplines. Its diagnostic significance is indicated by the fact that it is a reversible medical condition if recognized early with an excellent response to immunosuppressive agents. Therefore, it should be considered in the differential diagnosis of hearing disorders especially in the context of another autoimmune disease such as Hashimoto's thyroiditis.